Patterns of shape composition in architecture - Balykbaev, Baizhan; Sultanova, Kamilya; Maulenova, Gulnara; Sarzhanov, Niyaz (project baikal, 2023)
The article deals with the essential regularities of form making in architecture. The authors outline two logics of aesthetic organisation of visual material. One logic goes from inside to outside – from the internal structure of the object to its external form as a system of information expression of the functional and planning organisation and structure; the other logic goes from outside – from the artistic and figurative solution for the architectural environment of the town-planning complex to the building, to its tectonics and geometric form. The analysis of modern architectural practice gives the authors an idea that the true architectural form should be sought beyond the styles and that extra-architectural associations today may be much more fruitful than turning to the trendiest styles.